2021
DOI: 10.1128/mra.00058-21
|View full text |Cite
|
Sign up to set email alerts
|

Chromosome-Scale Assembly of the Complete Genome Sequence of Leishmania ( Mundinia ) martiniquensis , Isolate LSCM1, Strain LV760

Abstract: Leishmania ( Mundinia) martiniquensis is a kinetoplastid parasite that was first isolated in 1995 on Martinique. We report the first complete genome for Leishmania martiniquensis from Asia, isolate LSCM1, strain LV760, which was sequenced using combined short-read and long-read technologies. This will facilitate greater understanding of the evolution of the geographically dispersed subgenus Mundinia .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…This study also found that the de Bruijn graph-based MEGAHIT program was another good assembler for the Leishmania genome compared to SPAdes which was used several times in our workflow, consistent with the report that the MEGAHIT program could handle large and complex next-generation sequencing datasets [ 51 ]. In contrast, several recent chromosome-scale Leishmania genomes, including L. orientalis isolate LSCM4, were assembled using de novo assembly of the long-read MinION data as guidance for mapping the Illumina short reads [ 45 ]. In this study, our assembled genome of L. orientalis isolates PCM2 from the proposed analytic workflow on the short-read data shared highly similar genomic synteny with those of the LSCM4, as shown in Figure 3 , implying the genome structural similarity between the selected reference, L. enriettii , and the LSCM4 genome.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study also found that the de Bruijn graph-based MEGAHIT program was another good assembler for the Leishmania genome compared to SPAdes which was used several times in our workflow, consistent with the report that the MEGAHIT program could handle large and complex next-generation sequencing datasets [ 51 ]. In contrast, several recent chromosome-scale Leishmania genomes, including L. orientalis isolate LSCM4, were assembled using de novo assembly of the long-read MinION data as guidance for mapping the Illumina short reads [ 45 ]. In this study, our assembled genome of L. orientalis isolates PCM2 from the proposed analytic workflow on the short-read data shared highly similar genomic synteny with those of the LSCM4, as shown in Figure 3 , implying the genome structural similarity between the selected reference, L. enriettii , and the LSCM4 genome.…”
Section: Discussionmentioning
confidence: 99%
“…Despite concerns about the genetic variation of L. orientalis and their public health impacts, genomic information of multiple L. orientalis isolates has gained attention. To date, three major genome sequencing platforms (Illumina, PacBio, and Oxford Nanopore) have been used to create the complete genomic data of several Leishmania species, including the genome of L. major strain Friedlin [ 31 , 42 , 43 , 44 ], L. infantum strain JPCM5 [ 33 , 42 ], L. martiniquensis strain LSCM1 [ 45 , 46 , 47 ], and a recent L. orientalis strain LSCM4 isolated from the northern province of Thailand [ 46 , 47 , 48 ], in exchange for considerable cost invested in the genome project. Questions have arisen on whether the new Leishmania species shall have their whole genomes decoded using all techniques at first glance.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, highly accurate genomes for L. martiniquensis and L . orientalis, isolated in northern Thailand, were reported [ 54 , 55 ]. In this study, however, candidate antigens were selected based on the data from draft genomes of the two species isolated in southern Thailand [ 25 ], and more candidates may be found if highly accurate sequence information becomes available.…”
Section: Discussionmentioning
confidence: 99%
“…De novo assembly was performed using SPAdes version 3.12.0 [ 20 ]. The scaffold sequences from the previous step were used to align with the Leishmania martiniquensis genome from the NCBI database (accession number CM030396.1–CM030431.1 for chromosome 1–36) [ 21 ] using the Artemis comparison tool (ACT) [ 22 ]. In addition, the Illumina reads were mapped into the assembled scaffolds using BWA version 0.7.16a [ 23 ].…”
Section: Methodsmentioning
confidence: 99%